Development of Khulafaur Rasyidin Smartcard Learning Media to Enhance Students’ Cognitive Abilities in the Islamic Cultural History (SKI) Subject for Grade V - Rahmah, Fitria Nur; Rosyidah, Binti (PGMI, STAI Miftahul Ula Nganjuk, 2024)
Technological advancements require the education sector to continuously adapt, including in the development of learning media. The use of conventional and monotonous learning media causes students to lose enthusiasm, which in turn affects their level of understanding. The lack of students’ interest in history subjects and limited interaction between teachers and students serve as the background of this study. In addition, limited instructional time and students’ low interest in reading books make the development of innovative learning media highly relevant. Therefore, the researcher conducted a research and development study to develop Smartcard learning media to enhance students’ cognitive abilities in the Islamic Cultural History (SKI) subject for Grade V at SD IT Al-Furqon Garu, Baron, Nganjuk. This study aims to examine: (1) the development of Smartcard learning media for the SKI subject on the topic of Khulafaur Rasyidin for Grade V students at SD IT Al-Furqon Garu, Baron, Nganjuk in the 2023/2024 academic year; (2) the validation of Smartcard learning media for the same subject and topic; and (3) the effectiveness of Smartcard learning media in improving students’ cognitive abilities. This research employed a Research and Development (R&D) approach. The development model used in this study refers to the 4-D model proposed by Thiagarajan, which consists of four stages: (1) Define, (2) Design, (3) Develop, and (4) Disseminate. Data collection instruments included validation questionnaires administered to media experts and material experts, as well as pre-test and post-test instruments given to students to measure the effectiveness of the developed product. The data analysis technique used was quantitative analysis to assess the validity and effectiveness of the product. The result of this research and development is a learning medium called Smartcard Khulafaur Rasyidin, which contains SKI learning materials presented in the form of smart cards. Product validation by material and media experts obtained an overall average percentage score of 91%, indicating that the product is valid. Furthermore, the calculation of the N-gain score from the pre-test and post-test results yielded a value of 0.80 or 80.51%, indicating that the developed product falls into the “high” score category and demonstrates an “effective” level of effectiveness.